MENGUATKAN EKONOMI KELUARGA MELALUI PEMBUATAN ECO PAVING BLOCK BERBASIS NILAI AN-ZAHFATU MINAL IMANDI DESA TANJUNG MEDANG KECAMATAN KELEKAR KABUPATEN MUARA ENIM - Iin Fadlilah; Salman Al-Farisi; Fadhil Al-Mustaqim; Delia Sabila; Dwi Fitri Anggraini; Dwi Zaharani; Tiara Kusuma (CV. Denasya Smart Publisher, 2026)
Family economic challenges and the increasing volume of plastic waste pose challenges that require innovative and sustainable solutions. This program aims to strengthen family finances through the creation of eco-paving blocks based on the values ​​of An-Zahfatu Minal Iman (The Faithful Belief), which serve as a spiritual foundation for maintaining environmental cleanliness. The methods used include outreach, technical training in processing plastic waste into paving blocks, and mentoring in family business management. Results demonstrate that utilizing plastic waste can produce valuable products, increase family income, and raise public awareness of the importance of cleanliness as part of faith. Thus, this program not only improves economic well-being but also encourages the creation of a clean, productive, and sustainable environment.